Pengembangan Perangkat Layanan Bimbingan Klasikal untuk Meningkatkan Kemandirian Belajar Siswa - I Kadek Doniarta; I Ketut Gading; Kadek Ari Dwiarwati (Jurnal Bimbingan dan Konseling Indonesia, 2022)
This research is a research & development research. The product developed is the Classical Guidance Service Tool to improve Students' Independent Learning. The development in this study uses a 4D model. The subjects of this study were 3 Counseling Guidance Lecturers and 2 Counseling Guidance Teachers at SMP. The data collection method in this study was using a questionnaire. The acceptance of the classical guidance service apparatus found that the results of the CVR index calculation showed that the total total score was 45, so that the CVI calculation obtained the result 1. The results of the t-test data in the table, the probability value or Sig. (2-tailed) is 0.000, the probability value is this is more than the 0.05 level of significance. Thus, it is effective to increase student learning independence, to test classical tutoring tools to increase student learning independence. The acceptance of the classical guidance service apparatus is a high or low assessment of the usefulness, accuracy, and accuracy of the apparatus which includes: RPL, service materials, media services, LKPD, and evaluation tools.